2021
DOI: 10.3390/biology10070673
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about Fibromyalgia in Fibromyalgia Patients and Its Relation to HRQoL and Physical Activity

Abstract: Introduction: Fibromyalgia (FM) affects 2.40% of the Spanish population. The most widespread treatment has been the combination of patient education, pain coping strategies and exercise. With regard to patient education, there are few previous studies on the efficacy of relating FM education in isolation with an improvement in FM, although there are some studies that report that health education programs could modify the perception of quality of life and improve pain. Objectives: the aim was to find out the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…These findings are supporting the first research hypothesis. This finding is consistent with the study by Mendoza-Muñoz et al (2021) (2) , which examined "the relationship between fibromyalgia knowledge, health-related quality of life (HRQoL), and physical activity" . They found that participants had an overall medium (49%) to high (41%) level of FM knowledge, with the majority having low knowledge in areas related to medicine and energy.…”
Section: Figuresupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are supporting the first research hypothesis. This finding is consistent with the study by Mendoza-Muñoz et al (2021) (2) , which examined "the relationship between fibromyalgia knowledge, health-related quality of life (HRQoL), and physical activity" . They found that participants had an overall medium (49%) to high (41%) level of FM knowledge, with the majority having low knowledge in areas related to medicine and energy.…”
Section: Figuresupporting
confidence: 92%
“…This outcome was consistent with research done in 2023 by Smith and Croucamp (16) to study the life quality and physical functioning of patients with fibromyalgia and noted that there is a weak association between role constraints brought on by emotional health and the FIQR, and a significant negative correlation between the two. Additionally, Mendoza-Muñoz et al (2021) (2) found that patients in Extremadura had a medium-high level of FM knowledge and that there was a direct correlation between FM patients' HRQoL (health-related quality of life) and their knowledge of physical activity. Furthermore, a study presented by Fonseca et al (2021) (25) showed that patients undergoing cognitive-behavioral therapy had improved FM impact as determined by FIQ.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Only awareness-level trials performed in Saudi Arabia were conducted among medical practitioners to investigate their ability to diagnose and manage FMS [ 29 , 30 ]. Also in other countries, the assessment of awareness and perception of FMS was set out among rheumatologists or among FMS Patients to explore the relationship between knowledge of HRQOL [ 31 , 32 ]. Data from our study revealed a higher rate of FMS among the Saudi Arabian population (7.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Two papers are on neuromuscular training programs (NMTs), training monotony (TM), and training strain (TS) in soccer players [ 2 , 3 ]; five articles provide innovative findings about testosterone and cortisol [ 4 , 5 ], gastrointestinal hormones [ 6 ], spirulina [ 7 ], and concentrations of erythroferrone (ERFE) [ 8 ]; another five papers analyze fitness and its association with other variables [ 7 , 9 , 10 , 11 , 12 ]; three papers examine body composition in elite female soccer players [ 2 ], adolescents [ 6 ], and obese women [ 7 ]; five articles examines the effects of high-intensity interval training (HIIT) [ 7 , 10 , 13 , 14 , 15 ]; one paper examines the acute effects of different levels of hypoxia on maximal strength, muscular endurance, and cognitive function [ 16 ]; another article evaluates the efficiency of using vibrating exercise equipment (VEE) compared with using sham-VEE in women with CLBP (chronic low-back pain) [ 17 ]; one article compares the effects of different exercise modes on autonomic modulation in patients with T2D (type 2 diabetes mellitus) [ 14 ]; and another paper analyzes the changes in ABB (acid–base balance) in the capillaries of kickboxers [ 18 ]. Other studies evaluate: the effects of resistance training on oxidative stress and muscle damage in spinal cord-injured rats [ 19 ]; the effects of muscle training on core muscle performance in rhythmic gymnasts [ 20 ]; the physiological profiles of road cyclist in different age categories [ 21 ]; changes in body composition during the COVID-19 [ 22 ]; a mathematical model capable of predicting 2000 m rowing performance using a maximum-effort 100 m indoor rowing ergometer [ 23 ]; the effects of ibuprofen on performance and oxidative stress [ 24 ]; the associations of vitamin D levels with various motor performance tests [ 12 ]; the level of knowledge on FM (Fibromyalgia) [ 25 ]; and the ability of a specific BIVA (bioelectrical impedance vector analysis) to identify changes in fat mass after a 16-week lifestyle program in former athletes [ ...…”
mentioning
confidence: 99%